2015
DOI: 10.1186/s40623-015-0348-2
|View full text |Cite
|
Sign up to set email alerts
|

Daytime gigahertz scintillations near magnetic equator: relationship to blanketing sporadic E and gradient-drift instability

Abstract: Observations made in non-equatorial regions appear to support the hypothesis that the daytime scintillation of radio signals at gigahertz (GHz) frequencies is produced by the gradient-drift instability (GDI) in the presence of a blanketing sporadic E (E sb ) layer. However, the only evidence offered, thus far, to validate this notion, has been some observations of E sb in the vicinity of GHz scintillations. A more comprehensive evaluation requires information about electric field, together with the presence of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
16
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(16 citation statements)
references
References 53 publications
0
16
0
Order By: Relevance
“…This theory has proven to work well in the midlatitude, where the inclination angle (I) is steep enough to produce Es layers (Whitehead, , ). Evidence regarding the midlatitude (Hajkowicz, , ; Hajkowicz & Minakoshi, ; Ogawa, Suzuki, & Kunitake, ), low latitude, and equatorial regions (Alfonsi et al, ; Huang, ; Kumar et al, ; Patel et al, , ; Seif et al, , , , ; Zou & Wang, ; Zou, ) have shown correlation between the occurrence of daytime scintillation and the Es layer. Nevertheless, thus far, very little is known about the nature of daytime L‐band scintillations and characteristics of Es at the magnetic dip equator, where wind shear theory fails to operate.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…This theory has proven to work well in the midlatitude, where the inclination angle (I) is steep enough to produce Es layers (Whitehead, , ). Evidence regarding the midlatitude (Hajkowicz, , ; Hajkowicz & Minakoshi, ; Ogawa, Suzuki, & Kunitake, ), low latitude, and equatorial regions (Alfonsi et al, ; Huang, ; Kumar et al, ; Patel et al, , ; Seif et al, , , , ; Zou & Wang, ; Zou, ) have shown correlation between the occurrence of daytime scintillation and the Es layer. Nevertheless, thus far, very little is known about the nature of daytime L‐band scintillations and characteristics of Es at the magnetic dip equator, where wind shear theory fails to operate.…”
Section: Introductionmentioning
confidence: 99%
“…Es can occur during daytime and nighttime. The occurrence of daytime Es can result in strong ionospheric scintillations (Aarons, 1982) even in the frequency range of gigahertz (GHz) (Kumar, Kishore, & Ramachandran, 2007;Seif et al, 2015;Zou, 2011;Zou & Wang, 2009). That is, during daytime, scintillation-producing irregularities are requiring a steep gradient associated with the background plasma-density profile, and a current driven by a neutral wind, where the Es layer is presumed to provide the exceptionally steep gradient particularly in the midlatitude.…”
Section: Introductionmentioning
confidence: 99%
“…At middle and low latitudes, a comprehensive study by Whitehead (1989) has shown that the E region ionization enhancements can be formed due to vertical shear caused by opposite horizontal neutral winds, which in turn can be driven by gravity waves (Hook 1970;Lanchester et al 1991;Jayachandran 1991) or tidal motions (Chimmonas 1971). The Es layers formed by wind shear lead to ionization enhancements that block the upper ionosphere to low-frequency radio soundings (Devasia et al 2004) and may lead to amplitude scintillations at gigahertz (GHz) frequencies (Seif et al 2015). Therefore, these layers are classified as blanketing layers (Es b ) (e.g., Devasia 1973, 1981;Rastogi 1997;Devasia et al 2004).…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, daytime scintillations were also found in both ground-based stations and space-borne observatories, with its unique cause compared with night time scintillations, as described by Basu and Dao [ 26 , 27 ]. Though most severe scintillation occurred at night side, the presence of daytime scintillation can’t be ignored, as stated by Seif [ 28 ]. In this section, daytime scintillation and its effects on loss of lock are discussed.…”
Section: Methodsmentioning
confidence: 99%